Dystocia by circular cord - Bazul, Víctor (2015)
In summary, three cases of dystocia are presented by circular lace: the first was an multiparous, with embedded vertex presentation, regular contractions, which in the course of work presents alterations in fetal heartbeat leading down to the minute and 84 the clinical examination suggests circular lace, and in which the acceleration of labor with Pitocin injection early rupture of the membranes allows the expulsion of a live fetus with a cord round the neck and the left upper limb. The second case is a primípara with embedded head, which begins its work with irregular contractions and abnormal fetal heart rate of 154 a minute, climbing to 170 irregular, barely noticeable, which is suspected of circular, that to be starting the work force in defense of the fetus to practice segmental cesarean live fetus extracted with two circular level left leg; the third refers to sew headed primípara deeply engaged with PROM who is induces labor, appearing after intense contractions disappear fetal heartbeats of 152, 160, 170 a minute, irregular, which suggests the presence of circular segmental practice requiring cesarean section, extracted with circular live fetus in the neck and in the left upper and lower limbs. The pathogenesis of dystocia was then studied by circular, its impact on pregnancy and delivery, fetal distress and ends pointing to the therapeutic approach to be followed.